Kajian Kapasitas Tukar Kation (KTK) dan Rasio C/N pada Aplikasi Pupuk Cair Bonggol Pisang (Musa sp.) dan Mikoriza di Pembibitan Awal Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) - Sylvia Madusari (JURNAL CITRA WIDYA EDUKASI, 2018)
Nutrient availability in the soil is influenced by soil physical and chemical properties. Cation exchange capacity (CEC), base saturation (BS), content of organic C, degree of soil acidity (pH) and C/N ratio are some chemical properties of growing media which can be an indicator of the availability of nutrients to the growing media and fertility growing media. Use of subsoil has not been done because the nutrient content is low. The addition of mycorrhizae and liquid fertilizer derived from banana tree corm could affect the decomposition of organic matter and nutrient supply to the growing media so that nutrients are absorbed by plants is high. The results showed that the observation of 3 MAP, the highest CEC value, amounting to 15 cmolc/kg achieved in P4 treatment. The growing media with liquid fertilizer and mycorrhizal banana tree stump showed that the highest CEC value is 12.72 cmolc/Kg achieved by treatment P6. Application of liquid fertilizer and mycorrhizal banana corm to the growing media subsoil and manure mixture has a C/N ratio 14, higher than the C/N ratio in the same planting medium without giving liquid fertilizer and mycorrhizal banana tree corm, ie 12. The dry weight oil palm seedlings highest in treatment P4.